Mathematics addendum - class 6 - Shenal, Don Celsus; Hsaan, Nosheen (Ideal furnishers, Karachi, 2022)
The addendum emphasizes the importance of regular practice, using visual aids, group study, and seeking help when necessary. It also suggests resources like textbooks, educational websites, and online tutorials to support learning. Overall, this guide aims to build confidence and understanding in Mathematics for Class 6 students.
This addendum serves as a supplementary guide for Class 6 Mathematics, aiming to reinforce key concepts and provide additional resources for students. It addresses important topics in the curriculum and offers tips for effective learning.
Keywords: Geometry; Data Handling